Acceptor Specificity of β-N-Acetylhexosaminidase from Talaromyces flavus: A Rational Explanation - Garcia-Oliva, Cecilia; Hoyos, Pilar; Petrásková, Lucie; Kulik, Natalia; Pelantová, Helena; Cabanillas, Alfredo H; Rumbero, Ángel; Křen, Vladimír; Hernáiz, María J; Bojarová, Pavla (International journal of molecular sciences, 2019)
Fungal β-N-acetylhexosaminidases, though hydrolytic enzymes in vivo, are useful tools in the preparation of oligosaccharides of biological interest. The β-N-acetylhexosaminidase from Talaromyces flavus is remarkable in terms of its synthetic potential, broad substrate specificity, and tolerance to substrate modifications. It can be heterologously produced in Pichia pastoris in a high yield. The mutation of the Tyr470 residue to histidine greatly enhances its transglycosylation capability. The aim of this work was to identify the structural requirements of this model β-N-acetylhexosaminidase for its transglycosylation acceptors and formulate a structure-activity relationship study. Enzymatic reactions were performed using an activated glycosyl donor, 4-nitrophenyl N-acetyl-β-d-glucosaminide or 4-nitrophenyl N-acetyl-β-d-galactosaminide, and a panel of glycosyl acceptors of varying structural features (N-acetylglucosamine, glucose, N-acetylgalactosamine, galactose, N-acetylmuramic acid, and glucuronic acid). The transglycosylation products were isolated and structurally characterized. The C-2 N-acetamido group in the acceptor molecule was found to be essential for recognition by the enzyme. The presence of the C-2 hydroxyl moiety strongly hindered the normal course of transglycosylation, yielding unique non-reducing disaccharides in a low yield. Moreover, whereas the gluco-configuration at C-4 steered the glycosylation into the β(1-4) position, the galacto-acceptor afforded a β(1-6) glycosidic linkage. The Y470H mutant enzyme was tested with acceptors based on β-glycosides of uronic acid and N-acetylmuramic acid. With the latter acceptor, we were able to isolate and characterize one glycosylation product in a low yield. To our knowledge, this is the first example of enzymatic glycosylation of an N-acetylmuramic acid derivative. In order to explain these findings and predict enzyme behavior, a modeling study was accomplished that correlated with the acquired experimental data.
Keywords: oligosacharidy; Protein Conformation; glykosidy; kinetika; Models, Molecular; Glycosides; beta-N-acetylhexosaminidasy; beta-N-Acetylhexosaminidases; Talaromyces; Glycosylation; Substrate Specificity; Oligosaccharides; glykosylace; molekulární modely; substrátová specifita; Kinetics; Structure-Activity Relationship; konformace proteinů; vztahy mezi strukturou a aktivitou